Pemberdayaan Lembaga Desa Dalam Pembangunan Sufrastruktur Di Kecamatan Rantau Badauh Kabupaten Barito Kuala - Mutia Rahmah (STIA Bina Banua Banjarmasin, 2020)
This research is describing the empowerment of village institution in the construction of superstructure. The problem formulation in this research are how the empowerment of village institution as well as the strengthening of human resource at th empowerment of village institution in the construction of superstructure at Rantau Badauh Sub-district of Barito Kuala District. This research used Juliannor Fatahillah, S.STP as the chief of Rantau Badauh Sub-district as the key informan and the informan are all of people who involve during research interraction. The focus of research are to know why the village institution at Rantau Badauh Sub-district is not encouraged maximally by government, is there any village that involve their institution in construction process, and the importance of role the village institution in construction process. Data collected are interview and documentary. Where analysis technique using descriptive qualitative. To get validity of data using Focus Group Discussion (FGD) at two village in Rantau Badauh Sub-disctrict such as Danda Jaya Village and Sungai Bamban Village. The result of this research show that the the process of empowerment village institution on the construction of superstructure at Rantau Badauh Sub-district Barito Kuala District goes according to the applicable rules and regulations, but there are differences on construction implementation at each village. The village intitution is not involved maxsimally on construction of superstructure. And the strengthening of human resource on construction of superstructure carried out at least one time every year with various activities. Penelitian ini menggambarkan tentang pemberdayaan lembaga desa dalam pembangunan suprastruktur. Rumusan masalah dalam penelitian ini adalah bagaimana pemberdayaan lembaga desa dalam pembangunan suprastruktur di Kecamatan Rantau Badauh Kabupaten Barito Kuala, bagaimana keterlibatan lembaga desa dalam siklus pembangunan suprastruktur di Kecamatan Rantau Badauh Kabupaten Barito Kuala, dan bagaimana penguatan sumber daya manusia pada pemberdayaan lembaga desa dalam pembangunan suprastruktur di Kecamatan Rantau Badauh Kabupaten Barito Kuala. Key Informan dalam penelitian ini adalah Bapak Juliannor Fatahillah, S.STP selaku Camat Rantau Badauh dan informan pada penelitian ini adalah semua yang terlibat dalam penelitian. Fokus penelitian ini adalah untuk mengetahui mengapa lembaga desa di Kecamatan Rantau Badauh belum diprioritaskan oleh pemerintah, apakah ada desa yang telah melibatkan lembaga desanya dalam proses pembangunan, dan pentingnya peranan lembaga desa dalam proses pembangunan. Adapun teknik pengumpulan data dalam penelitian ini adalah dengan wawancara dan dokumen. Teknik analisis data adalah deskriptif kualitatif. Untuk keabsahan data menggunakan Fokus Group Discussion (FGD) pada dua desa di Kecamatan Rantau Badauh Kabupaten Barito Kuala yaitu Desa Danda Jaya dn Desa Sungai Bamban. Hasil dari penelitian ini menunjukkan bahwa proses pemberdayaan lembaga desa dalam pembangunan suprastruktur di Kecamatan Rantau Badauh Kabupaten Barito Kuala berjalan sesuai aturan dan perundang-undangan yang berlaku, hanya saja ada beberapa perbedaan dalam pelaksanaan pembangunan pada masing-masing desa. Lembaga desa belum dilibatkan secara maksimal dalam pembangunan suprastruktur. Dan penguatan lembaga desa dilaksanakan paling sedikit satu kali dalam setahun dengan kegiatan yang berbeda-beda.